2014
DOI: 10.1016/j.ultsonch.2013.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sonication conditions: Solvent, time, temperature and reactor type on the preparation of micron sized vermiculite particles

Abstract: The effects of temperature, time, solvent and sonication conditions under air and Argon are described for the preparation of micron and sub-micron sized vermiculite particles in a double-jacketed Rosett-type or cylindrical reactor. The resulting materials were characterized via X-ray powder diffraction (XRD), Field Emission Scanning Electron Microscopy (FE-SEM), Fourier Transform Infrared (FTIR) Spectroscopy, BET surface area analysis, chemical analysis (elemental analysis), Thermogravimetry analysis (TGA) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(46 citation statements)
references
References 38 publications
6
37
0
3
Order By: Relevance
“…This indicated that the reduction of mean particle sizes by ultrasonic irradiation is less effective in irradiated media with high particle concentrations. Similar results were also reported, showing that higher particle concentrations enhanced the viscosity of irradiated media and hindered the cavitation effect (Ali et al, 2014).…”
Section: Resultssupporting
confidence: 80%
“…This indicated that the reduction of mean particle sizes by ultrasonic irradiation is less effective in irradiated media with high particle concentrations. Similar results were also reported, showing that higher particle concentrations enhanced the viscosity of irradiated media and hindered the cavitation effect (Ali et al, 2014).…”
Section: Resultssupporting
confidence: 80%
“…They were conditioned at 25 °C and 50% RH for at least 48 h before testing. Tensile tests were performed according to to a significant decrease of the particle sizes as observed by others [18,25]. The majority of the particles were irregular, but on the whole, they were convex shaped two-dimensional flakes.…”
Section: Characterizationmentioning
confidence: 87%
“…Vermiculite can also be exfoliated by treatment with H 2 O 2 [18,19]. Exfoliation into submicronic and even nanoflakes can be accomplished by subsequent sonication using high power ultrasound [18,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The vermiculite (0.4 mm mean diameter size, weighted amount of 0.55 g or 3.85 g) was sonicated at room temperature in 55 mL hydrogen peroxide (35%) in a "Rosett" type glass double-jacketed reactor cooled at 25°C by circulation of a cryogenic fluid, using a Sonotrode (20 kHz, 350 W, Ti ultrasonic probe, Sonics and Materials, 43 mm amplitude, 56 W acoustic power) in order to produce small particles (Nguyen et al, 2013;Ali et al, 2014;Nguyen et al, 2014). The solid/liquid (S/L) ratio and the sonication time were varied in order to modify the particle size distributions.…”
Section: Vermiculite Powdersmentioning
confidence: 99%